inggris - Asrial, An Aldia; Pudjiastuti, Anggit; Herry, Yan; Bahrudin, Udin (Jurnal Kardiologi Indonesia, 2022)
Background Zwolle, TIMI, and GRACE risk scores have been proven to predict mayor adverse cardiovascular events (MACE) in STEMI patients undergoing primary percutaneous coronary intervention (PCI). However, they were developed over a long time ago which many advances have been made in the cardiovascular field today. The scores were also developed in the non-Asian majority population and their accuracy for Indonesian population remains unknown. We aimed to validate and compare these scores for Indonesian population. Methods An analytical observational study was conducted on 193 patients undergoing primary PCI. The Zwolle, GRACE, and TIMI risk scores were calculated for each patient. Then, the risk score validation was carried out with the calibration test using Hosmer Lemeshow test and discrimination test using the AUC ROC. Furthermore, the comparisons between the risk scores were carried out using the DeLong test. Results The three scores have good results in the Hosmer Lemeshow calibration test (p > 0.05). The discrimination test also indicated good results with AUC ROC Zwolle, TIMI and GRACE risk scores respectively 0.776; 0.782; 0.831 (p<0.05). There was no significant difference in the prediction accuracy of the three risk scores in the DeLong test. Conclusions The Zwolle, TIMI, and GRACE risk scores had good validity for predicting major adverse cardiovascular events in STEMI patients undergoing primary PCI. There was no significant difference in the prediction accuracy of the three risk scores. This article has a related Erratum.